Accuracy of Intraocular Lens Power Calculation Formulas in Pediatric Cataract Patients: A Systematic Review and Meta-Analysis - Zhong, Yueyang; Yu, Yibo; Li, Jinyu; Lu, Bing; Li, Su; Zhu, Yanan (Frontiers in Medicine, 2021)
Background Among the various intraocular lens (IOL) power calculation formulas available in clinical settings, which one can yield more accurate results is still inconclusive. We performed a meta-analysis to compare the accuracy of the IOL power calculation formulas used for pediatric cataract patients. Methods Observational cohort studies published through April 2021 were systematically searched in the PubMed, Web of Science, and EMBASE databases. For each included study, the mean differences of the mean prediction error and mean absolute prediction error (APE) were analyzed and compared using the random-effects model. Results Twelve studies, involving 1,647 eyes, were enrolled in the meta-analysis, and five formulas were compared: Holladay 1, Holladay 2, Hoffer Q, SRK/T, and SRK II. Holladay 1 exhibited the smallest APE (0.97; 95% confidence interval [CI]: 0.92 to 1.03). For the patients with an axial length (AL) less than 22 mm, SRK/T showed a significantly smaller APE than SRK II (mean difference [MD]: -0.37; 95% CI: -0.63 to -0.12). For the patients younger than 24 months, SRK/T had a significantly smaller APE than Hoffer Q (MD: -0.28; 95% CI: -0.51 to -0.06). For the patients aged from 24–60 months, SRK/T presented a significantly smaller APE than Holladay 2 (MD: -0.60; 95% CI: -0.93 to -0.26). Conclusion Due to the rapid growth and high variability of pediatric eyes, the formulas for IOL calculation should be considered according to clinical parameters such as age and AL. The evidence obtained supported the accuracy and reliability of SRK/T under certain conditions.